(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the role of the idea of the “Mature Individual” in the moral and spiritual education of students. It analyzes how the concept of the Mature Individual can be applied in the educational process and its influence on the formation of moral values. The article emphasizes the importance of interactive methods, role modeling, and spiritual discussions, and offers practical recommendations.